Multivariate data analysis - Hair, Joseph F.; Anderson, Rolph E.; Tatham, Ronald L.; Black, William C. (London : Prentice Hall International, Inc., 1998)
Computer Science
Includes index
1999-11-30
Keywords: Data Analysis; Multimedias